The ageing of the population and the fertility in Poland - Podogrodzka, Małgorzata (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
From the 1990s. we note the considerable decrease in the fertility rate in Poland and the rise in the proportion of persons aged 60 years and more in population. The article is to demonstrate the dynamics of changes of both processes and to correlation between the two processes. For the description of the changes in the value of the fertility rate and the share of persons aged over 60 years we use a linear function of the trend, and to describe the relationship of both processes multiple linear regression.